Haplotypic polymorphisms and forensic applications in Chinese Hunan Han population based on a series of Y-STR loci: a perspective of paternal inheritance - Ming Zhao; Wei Cui; Yunying Zhang; Qiong Lan; Bofeng Zhu (Taylor & Francis Group, 2023)
Background Hunan, a multinational province in China, possesses more than fifty ethnic groups, such as the Han, Yao, Tujia, Miao, and so on. Aims To evaluate the forensic efficiency of the novel panel and investigate the genetic relationships between Hunan Han population and 12 other reference populations from China. Subjects and methods Haplotypic data of 153 unrelated males of Hunan Han population were investigated using the AGCU Y SUPP Plus amplification system containing 27 Y-chromosomal short tandem repeat (STR) loci. Forensic parameters were calculated to evaluate the application efficiency of this panel in Hunan Han population. Results Haplotype diversity, discrimination capability, and match probability values were 0.9999999977, 1.0000, and 0.0065, respectively. Pairwise fixation index values demonstrated that the minimal genetic differentiation (0.0073) was found between Hunan Han population and Hunan Yao group, while the maximal genetic differentiation (0.0651) was observed between Hunan Han and Guangxi Yao group from the perspective of the patrilineal DNA analysis. Conclusions The haplotype distributions of 27 Y-STR loci in Hunan Han population exhibited remarkable polymorphisms. Moreover, this panel has potential advantages for the forensic applications regarding family investigations, paternity testing of the paternal line, and population genetics.